2017
DOI: 10.30958/ajh.4-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Diet Congruent Primes – Are They Effective? The Effects of Food Priming on Restrained Eaters’ Food Consumption

Abstract: This study examined the impact of healthy and unhealthy primes on the food choice of restrained and unrestrained eaters. Based on a literature review it was hypothesized that restrained eaters would be more susceptible to healthy primes. The reason for this hypothesis was that healthy primes would serve as a reminder of their diet and therefore promote healthy eating. To test the hypothesis, an experiment was carried out involving priming 92 subjects via posters with pictures of either healthy or unhealthy sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The aim of the current study was to examine if using healthy and unhealthy food images to prime word cues on an autobiographical memory test would in uence the proportion of speci c memories retrieved on this task. As images of healthy foods were expected to make restraint salient [32,33] and as restraint has been linked to reduced memory speci city [10,26], it was predicted that, after controlling for depression, individuals primed with healthy images would retrieve signi cantly fewer speci c memories than would participants primed with unhealthy images. This prediction was supported by the current ndings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the current study was to examine if using healthy and unhealthy food images to prime word cues on an autobiographical memory test would in uence the proportion of speci c memories retrieved on this task. As images of healthy foods were expected to make restraint salient [32,33] and as restraint has been linked to reduced memory speci city [10,26], it was predicted that, after controlling for depression, individuals primed with healthy images would retrieve signi cantly fewer speci c memories than would participants primed with unhealthy images. This prediction was supported by the current ndings.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction was supported by the current ndings. However, as priming of restraint should have been more evident in those with high restraint scores [32] it was expected that individuals with higher restraint scores in the healthy prime condition would exhibit poorer memory speci city than would those with low restraint scores. This prediction was not supported by the current data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in another study, females consumed fewer calories after being primed with words connoting healthy body image (e.g., slim) than neutral primes (e.g., room) [ 31 ]. Interestingly, priming participants with images of healthy snacks (compared to unhealthy) increased restraint in restrained eaters, but not unrestrained eaters [ 32 ]. A review of the priming literature confirmed the effectiveness of low-calorie foods in priming restraint [ 33 ].…”
Section: Introductionmentioning
confidence: 99%